An adjunctive minor surgical procedure for increased rate of retraction - Prabhakar Krishnan; Sandeep Shetty; Akhter Husain (Journal of Pharmacy and Bioallied Sciences, 2013)
Introduction: Orthodontic treatment is based on the principle that if prolonged pressure is applied to the tooth, tooth movement will occur as the bone around the tooth re-models. In this study osteotomy of buccal alveolar plate and undermining of interseptal bone was performed at premolar extraction site and rate of en-masse retraction and canine retraction was evaluated. Materials and Methods: Patients between the age of 18 and 25 years, requiring retraction of anterior teeth are selected for the study. Osteotomy with undermining of interseptal bone at the extraction site was performed. The procedure was performed on all four quadrants. Results: The average retraction in the maxillary arch was 0.98 mm/quadrant in 3 weeks, i.e., a total retraction of 5.89 mm in a span of 9 weeks. The average retraction in the mandibular arch was 0.96 mm/quadrant in 3 weeks, i.e., a total retraction of 5.75 mm in a span of 9 weeks. Conclusion: This method of achieving faster en masse retraction immediately after extraction definitely reduced the initial retraction time. We recommend that such procedure must be carried out with appropriate anchorage conservation methods.